Legal Review of the Punishment of Perpetrators of Criminal Acts of Assault Resulting in Serious Injuries (Study of Decision No: 334/Pid.B/2023/PN.Amb and Decision No: 30/Pid.B/2023/PN.Cjr) - Ashadiqi, Rafi; Tri Bawono, Bambang (UNISSULA Semarang, 2025)
Abstract. The crime of assault causing serious injury as regulated in Article 351 paragraph (2) of the Criminal Code (KUHP) is a form of crime against the body which has serious consequences for the victim. This study aims to analyze the legal construction of the crime of assault causing serious injury and to evaluate the application of the principle of legal certainty in court decisions. The research method used is a normative legal approach with descriptive-analytical specifications and case study techniques. The object of the study is focused on the Study of Decision No: 334 / Pid.B / 2023 / PN.Amb and Decision No: 30 / Pid.B / 2023 / PN.Cjr with an analytical approach to the elements of the crime, evidence, judges' considerations, and their relevance to the principles of legality, proportionality, and legal certainty. The results of the study show that the elements in Article 351 paragraph (2) of the Criminal Code are formally proven, but their application in material aspects is often inconsistent because it depends on the judge's subjective interpretation of the victim's injury conditions. This difference creates disparities in sentencing and weakens the principle of legal certainty. Therefore, this thesis recommends the importance of strengthening guidelines for interpreting material criminal law related to serious injuries, as well as harmonization between the results of the post-mortem and the legal construction in the decision in order to create a fair, proportional, and legally certain sentencing system.